ISOLASI Steinernema DARI TANAH PERTANAMAN JAGUNG DI BENGKULU BAGIAN SELATAN DAN PATOGENESITASNYA TERHADAP Spodoptera litura F. - Djamilah Djamila; Nadrawati Nadrawati; Muhammad Rosi (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2010)
[THE ISOLATION OFSteinernema FROM CORN FIELD AND ITS PATHOGENECITY TO Spodoptera litura F]. Insect pathogenic nematode (IPN) offers an environmentally sound of controlling insect pest, as alternative for chemical insecticide. This research was conducted to evaluate the effectiveness of Steinernema sp isolates collected from corn fields in Southern parts of Bengkulu Province. The factorial experiment involved treatment combinations between sources of IPN isolate (Seluma, South Bengkulu, and Kaur) and density of IPN isolate (100, 200, and 400 JI mL-1). The pathogenecity of the isolates were tested by inoculating the isolates on 4th instar of S. litura. The isolate of IPN collected from Seluma and Kaur corn fields were more effective in controlling the insect compared to those of the South Bengkulu as S. litura was killed faster and caused the 100 % mortality at 60 hours after inoculation. The symptoms of attacked larvae of S. litura were sluggish movement, body color changed to blackish with damaged internal organs. (JI=juvenile infective)